The use of contextualised teaching and learning in grade 11 and 12 mathematics classrooms in Gobabis, Namibia (Journal for Studies in Humanities and Social Sciences, 2015)
This paper investigates the use of contexts in the teaching and learning of mathematics in two secondary schools in the Gobabis area using the Mayoh & Knutton (1997) taxonomy. It was found that not all contexts as suggested by Mayoh & Knutton were used by the teachers and that the context were almost entirely initiated by the mathematics teachers and were used as a primary strategy for presenting the content. The study recommended the introduction of the use of contexts in the pre-service training of mathematics teachers and that teachers create their own mathematics problems to solve rather than adhering to the problems provided in their textbooks which are often of a foreign origin.